Pelatihan Dan Pendampingan Ibu PKK Memanfaatkan Lahan Kosong Di Taman Sidoarjo - Sri Rahayuningsih; Dyah Rini Prihastuty (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Nowadays, there is a lot of participation of women in various fields, and the results are quite amazing. It turns out that women also have hidden abilities that can still be explored apart from cooking. So on this occasion we will provide training to PKK mothers in Sidoarjo Park, namely by holding fish farming training, simple bookkeeping and financial management assistance. Our community service team aims to motivate PKK mothers to earn additional income by utilizing empty land. The community service team also aims to make PKK mothers smart in managing business finances. The description above is the aim of our community service team to help Mrs. PKK progress in managing the business, so that it can generate additional income.